EMPTY BENCH IN INDONESIAN PERFORMING ARTS STUDIES: AUDIENCE - Dhani, Kurnia Rahmad (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2021)
Many Indonesian performing art experts have stated that audience studies were conducted in minimal numbers. However, the exact number of research on performing art audiences in Indonesia remains unclear. The factors that influence it are still not known in detail. This paper used a literature review on seven nationally accredited performing arts journals from art institutes in Indonesia over the past ten years. The results showed that only 3 out of 1034 journal titles focusing on performing art audiences in the last ten years. From these findings, we can conclude that the study on the audiences is so scarce. This research theme is not interesting for performing art experts in Indonesia. Indonesian performing art experts and academicians have left the importance of audience studies. This paper also discusses the factors that influence the negligible of performing arts audience studies in Indonesia.